2006
DOI: 10.2527/jas.2006-118
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of myostatin during development and regeneration of skeletal muscle in Japanese Black Cattle1

Abstract: Myostatin is a specific negative regulator of skeletal muscle growth and is regarded as one of the most important factors for myogenesis. The aim of the current study was to analyze the developmental change in the gene expression of myostatin and an adipogenic transcription factor (peroxisome proliferator-activated receptor lambda2) in the semitendinosus muscle of Japanese Black Cattle throughout the whole life cycle. An additional aim was to compare the temporal expression patterns of myostatin and relevant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
21
1
1
Order By: Relevance
“…The disconnect between the MRFs response in relation to the myostatin may have resulted from impaired muscle response due to injury and/or, as noted, due to the short rest interval between the exercise bouts. In contrast to this observation, Shibata et al (2006) reported diVerent expression patterns between myostatin and MRFs during muscle regeneration in Japanese-cattle.…”
Section: Myostatincontrasting
confidence: 67%
“…The disconnect between the MRFs response in relation to the myostatin may have resulted from impaired muscle response due to injury and/or, as noted, due to the short rest interval between the exercise bouts. In contrast to this observation, Shibata et al (2006) reported diVerent expression patterns between myostatin and MRFs during muscle regeneration in Japanese-cattle.…”
Section: Myostatincontrasting
confidence: 67%
“…The data for MYOD1 , MYOG and MYF5 are consistent with the analyses reported in other species [Weintraub et al, 1991;Shibata et al, 2006] and suggest that in the adult muscle, all these genes are expressed mainly in satellite cells, but not in the myonuclei that sustain the myofiber [Zammit et al, 2004].…”
Section: Expression Analyses and Regulative Sequence Conservation Comsupporting
confidence: 78%
“…Beta-catenin is an important protein that functions as a transcription factor, causing cellular growth both in the embryo and postnatally (Armstrong & Esser, 2005). Conversely, a member of the transforming growth factor-β superfamily, myostatin, is an important regulator of myogenesis, acting as an inhibitor of skeletal muscle growth (McPherron, Lawler, & Lee, 1997;Shibata et al, 2006). Other proteins of interest within muscle were muscle ring finger 1 (MuRF1) and muscle atrophy F-box (MAFbx) proteins.…”
Section: Rna Extraction Real Time-pcr and Gene Expression Analysismentioning
confidence: 99%